Rocky Mountain spotted fever in Mexican children: Clinical and mortality factors. - Gerardo Álvarez-Hernández; María del Carmen Candia-Plata; Jesús Delgado-de la Mora; Natalia Haydeé Acuña-Meléndrez; Anabel Patricia Vargas-Ortega; Jesús David Licona-Enríquez (Instituto Nacional de Salud Pública, 2016)
Objective. Characterize clinical manifestations and predictors of mortality in children hospitalized for spotted fever. Materials and methods. Cross-sectional study in 210 subjects with a diagnosis of Rocky Mountain spotted fever (RMSF) in a pediatric hospital in Sonora, from January 1st, 2004 to June 30th, 2015. Data were analyzed using descriptive statistics and multivariate logistic regression. Results. An upward trend was observed in RMSF morbidity and mortal- ity. Fatality rate was 30%. Three predictors were associated with risk of death: delay ≥ 5 days at the start of doxycycline (ORa = 2.95, 95% CI 1.10-7.95), acute renal failure ((ORa = 8.79, 95% CI 3.46-22.33) and severe sepsis (ORa = 3.71, 95% CI 1.44-9.58). Conclusions. RMSF causes high mortality in children, which can be avoided with timely initiation of doxycycline. Acute renal failure and severe sepsis are two independent predictors of death in children with RMSF.